No Evidence That Frontal Eye Field tDCS Affects Latency or Accuracy of Prosaccades - Reteig, Leon C.; Knapen, Tomas; Roelofs, Floris J. F. W.; Ridderinkhof, K. Richard; Slagter, Heleen A. (Frontiers in Neuroscience, 2018)
Transcranial direct current stimulation (tDCS) may be used to directly affect neural activity from outside of the skull. However, its exact physiological mechanisms remain elusive, particularly when applied to new brain areas. The frontal eye field (FEF) has rarely been targeted with tDCS, even though it plays a crucial role in control of overt and covert spatial attention. Here we investigate whether tDCS over the FEF can affect the latency and accuracy of saccadic eye movements. 26 participants performed a prosaccade task in which they made eye movements to a sudden-onset eccentric visual target (lateral saccades). After each lateral saccade, they made an eye movement back to the center (center saccades). The task was administered before, during and after anodal or cathodal tDCS over the FEF, in a randomized, double-blind, within-subject design. One previous study (Kanai et al., 2012) found that anodal tDCS over the FEF decreased the latency of saccades contralateral to the stimulated hemisphere. We did not find the same effect: neither anodal nor cathodal tDCS influenced the latency of lateral saccades. tDCS also did not affect accuracy of lateral saccades (saccade endpoint deviation and saccade endpoint variability). For center saccades, we found some differences between the anodal and cathodal sessions, but these were not consistent across analyses (latency, endpoint variability), or were already present before tDCS onset (endpoint deviation). We tried to improve on the design of Kanai et al. (2012) in several ways, including the tDCS duration and electrode montage, which could explain the discrepant results. Our findings add to a growing number of null results, which have sparked concerns that tDCS outcomes are highly variable. Future studies should aim to establish the boundary conditions for frontal eye field tDCS to be effective, in addition to increasing sample size and adding additional controls such as a sham condition. At present, we conclude that it is unclear whether eye movements or other aspects of spatial attention can be affected through tDCS of the frontal eye fields.